Evaluation of Psychiatrist’s Communication with Psychosis Patients - Karatas, Mehmet; Kartalci, Sukru; Selcuk, Engin Burak; Yetis, Hakan; Karatas, Turgay; Gozukara, Harika (Acta Bioethica, 2022)
Evaluation of the physician-patient relationship is very important in determining priorities in medical practice and medicine. For this purpose, in this study the psychiatrist’s communication with psychotic patients as a sensitive group was evaluated. A questionnaire was administered to 210 patients in a psychiatric clinic of Inonu University Hospital in Turkey to determine how the examination is performed in the facility for outpatients in the psychosis unit. According to the study conducted, it was observed that the evaluation score of the psychiatrist's communication with psychotic patients increased positively with increasing consultation duration. Our work is particularly noteworthy because it deals with a sensitive area, such as a group of psychiatric patients. The scores were obtained based on data from the evaluation of the questionnaires, which showed that the communication between the psychiatrist and the psychotic patient was conducted in a sensitive and careful manner, and without ethical problems.